ANALISIS KEMAMPUAN BELAJAR OPERASI HITUNG PERKALIAN PADA PESERTA DIDIK KELAS 4D SDN KEMAYORAN 1 BANGKALAN - Putri, Sheila; Isna Ida Mardiyana; Siska Trisnayanti (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2024)
This research aims to find out more about the ability to learn multiplication calculation operations in class 4D students at SDN Kemayoran 1 Bangkalan. The method used during the research was descriptive qualitative method. With the article that the researcher has presented, students' understanding of the mathematical operations of multiplication is very good. Even during learning, they are very enthusiastic and active when the teacher gives questions about multiplication. The research results show that during learning, students are very enthusiastic and active when the teacher gives questions about multiplication. For researchers, arithmetic operations are initial material and also very important material for students to be able to start learning mathematics. By mastering the material on arithmetic operations, students will also make it easier to accept and continue other mathematical material. This is very important to become a basis for students and also to implement it in the community because mathematical skills are really needed in everyday life.